PROVOCAÇÕES PARA UMA EDUCAÇÃO SENSÍVEL: O OLHAR DO GESTOR PARA O NÃO DITO - Marchetto, Cesar Augusto Di Senzi (2009)
To be the subject and the object of your researcher and educator practice. This is aim of the research made in this paper, through stories of lives and the importance of how the educator see it, to understand the importance of sensibility in the constitution of the subject-author, of a sensitive and democratic management. In the process of citizens-authors’s formation, it is necessary to consider the way we look and understand the world. The relation between teaching and learning, the relation between fellows, to democratic and to carry a meaning must consider that, in way this relation happens in the teaching-learning process. And as a way to know the sensibility, the experience in an artistic language, facing the pedagogical function that art has, appeasrs as a possibility to buid a meaning.(AU)